Multi-Level Governance in Achieving Regional Investment Targets: Analysis of Investment Realization in Lebak Regency 2020-2025 - Rusito Rusito; Jumanah Jumanah (Sean Institute, 2026)
This study aims to analyze Multi-Level Governance in achieving regional investment targets in Lebak Regency, Banten Province. The study employs a descriptive qualitative approach supported by quantitative data. The analysis focuses on five main dimensions of Multi-Level Governance, namely authority distribution, vertical coordination, horizontal coordination, policy integration, and implementation capacity. Data were collected through observation, in-depth interviews, documentation studies, and policy document analysis, and were supported by data on investment targets and investment realization in Lebak Regency for 2021-2025 as well as Investment Activity Report (LKPM) data for 2020-2025. The findings show that the achievement of regional investment targets in Lebak Regency reflects a relatively functioning practice of Multi-Level Governance, particularly through the distribution of authority across levels of government, the linkage between central and local policies, coordination across regional government agencies, the support of local investment regulations, and the basic capacity to implement investment policies. However, the study also finds that regional investment governance still faces challenges in terms of investment target synchronization, consistency of intergovernmental coordination, effectiveness of policy integration, and institutional capacity to diversify the investment structure, particularly in attracting Foreign Direct Investment (FDI). This study emphasizes that the achievement of regional investment targets should not be understood merely in terms of the nominal value of investment realization, but also as the outcome of a multi-layered governance system that shapes the effectiveness of regional investment policy.